2020
DOI: 10.1093/ehjci/ehaa946.2439
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in patients with cryptogenic stroke/TIA and subclinical atrial fibrillation

Abstract: Background A large proportion of patients with cryptogenic stroke or transitory ischemic attack (TIA) have underlying subclinical atrial fibrillation (SCAF) detected on follow up. It is not clear whether SCAF is the underlying primary entity in the pathogenesis of stroke in these patients, or merely a marker of atrial myopathy associated with left atrial remodeling, fibrosis and inflammation. Purpose As a hypothesis generatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies from mouse models have shown that the mice fed with a high-fat diet exhibited increased EMMPRIN expression, and in mice given neutralizing antibodies to EMMPRIN, lipid-filled atherosclerotic lesions were reduced in the aorta [35]. Limited data regarding EMMPRIN and history of arrhythmias or palpitations reported that in a small sample of patients with cryptogenic stroke or TIA who subsequently had subclinical atrial fibrillation, growth differentiation factor (GDF-15) correlated with premature atrial contractions and subclinical atrial fibrillation but not EMMPRIN [36]. This is in line with our findings where EMMPRIN was not associated with CVD.…”
Section: Association Of Biomarkers With Cvdmentioning
confidence: 99%
“…Studies from mouse models have shown that the mice fed with a high-fat diet exhibited increased EMMPRIN expression, and in mice given neutralizing antibodies to EMMPRIN, lipid-filled atherosclerotic lesions were reduced in the aorta [35]. Limited data regarding EMMPRIN and history of arrhythmias or palpitations reported that in a small sample of patients with cryptogenic stroke or TIA who subsequently had subclinical atrial fibrillation, growth differentiation factor (GDF-15) correlated with premature atrial contractions and subclinical atrial fibrillation but not EMMPRIN [36]. This is in line with our findings where EMMPRIN was not associated with CVD.…”
Section: Association Of Biomarkers With Cvdmentioning
confidence: 99%